Предмет: Математика,
автор: Vamp999
Помогите с В8, пожалуйста. Очень нужна помощь
Приложения:

Ответы
Автор ответа:
0
f(x)+g(x)=x²+3x+2
f(-x)=f(x), g(-x)=-g(x)
откуда получаем, что
f(-x)+g(-x)=f(x)-g(x)
f(x)+g(x)+(f (-x)+g(-x) )= f(x)+g(x)+f(x)-g(x)=2f(x)
получаем, что
f(x)=( f(x)+g(x)+(f (-x)+g(-x) ))/2=( x²+3x+2+ x²-3x+2)/2=(2x²+4)/2= x²+2
f(0,8)=0,8²+2=2,64
f(-x)=f(x), g(-x)=-g(x)
откуда получаем, что
f(-x)+g(-x)=f(x)-g(x)
f(x)+g(x)+(f (-x)+g(-x) )= f(x)+g(x)+f(x)-g(x)=2f(x)
получаем, что
f(x)=( f(x)+g(x)+(f (-x)+g(-x) ))/2=( x²+3x+2+ x²-3x+2)/2=(2x²+4)/2= x²+2
f(0,8)=0,8²+2=2,64
Автор ответа:
0
Спасибо вам)
Похожие вопросы